Atmospheric chemistry of perfluoronitriles: Environmental impact and experimental evidence related to N2O and NO formation - Chen, Liang (Elsevier, 2020)
The atmospheric chemistry of perfluoronitriles, the proposed replacement gases of SF6, has been investigated using an atmospheric reaction chamber. N2O formation was first observed following the reaction between perfluoronitriles and OH radicals, then NO formation was verified through experimentation. COF2, CF3C(O)F, and CO2 generation was observed, and a revised oxidation mechanism for perfluoronitriles in the atmosphere is proposed. Additionally, the rate coefficients related to OH radicals were measured for the perfluoronitriles of CF3CN, CF3CF2CN, CF3CF2CF2CN, and (CF3)2CFCN: their atmospheric lifetimes were 6.6, 10, 12, and 54 years, their radiative efficiencies were evaluated to be 0.188, 0.223, 0.317, and 0.231 W m−2 ppb−1, and their 100-year time horizon GWPs were 212, 374, 633, and 1705, respectively. The findings contained in this study indicate that perfluoronitriles present an insulating gas replacement option with a comparatively low environmental impact.